TRADITIONS OF SIENTIFIC SCHOOLS IN THE HISTORY OF SCIENCE DEPARTMENT OF PHARMACOLOGY OF PHARMACEUTICAL FACULTY OF THE I.M. SECHENOV FIRST MOSCOW STATE MEDICAL UNIVERSITY - A. A. Svistunov; N. P. Bykov (Сеченовский вестник)
The chair of pharmacology, faculty of pharmacy of the I.M. Sechenov First MSMU formed the Moscow school of teaching pharmacology at the Institute of Pharmacy and Pharmaceutical Institute, is a prestigious scientific pharmaceutical center. The article traces the course of the founders of the national schools of pharmacology (I.M. Dogel, N.P. Kravkov and others) developed by leading scientists (V.V. Nikolaev, M.P. Nikolaev, A.N. Kudrin) who worked at the department and created new scientific schools. The authors note the continuity of scientific traditions in the activities of the department in the course of its history. The information on the search for new approaches to the training of pharmacy, results of solving of some major issues of pharmacology are cited, which were the notable contribution of faculty in the biological and medical science.